Don Milani. For a discussion on lawfulness (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
In the editorial, Chief Editor Nando dalla Chiesa introduces issue 2/2023, which arose from the reflections and inputs that emerged during the conference dedicated to Don Milani and the legacy of "Letter to a Professor," held at the University of Milan on May 24, 2023.